CADMIUM-PEPTIDES COMPLEXES IN DUNALIELLA SALINA CELLS - M. Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Dunaliella salina responds to cadmium present in cells by synthesizing phytochelatin. Reverse Phase (RP)and common HPLC analysis describe the formation of complexes between Cd and γ-glutamyl peptides in cells. The unique peptides chain chelate Cd by thiolate bonds formation. Two classes of Cd-PCn complexes were identified as specific Cd-peptides complexes binding in D. salina.